Studying Overseas: Factors Impacting Intention of Female Students in Mainland China - Zhang, Yi (Leaf); Sun, Jie; Hagedorn, Linda Serra (Journal of International Students, 2013)
The purpose of this study was to investigate the factors that impact Chinese female students’ intention to study overseas. This study also aimed to understand how these factors impact female students’ decision making process. Using a survey questionnaire, data were collected from 96 female undergraduates who enrolled in a 4-year public university in North Central China fall 2010. Descriptive analyses, exploratory factor analyses, and structural equations modeling were utilized to answer the research questions. The results of the study indicated that students’ satisfaction with campus experience, English proficiency, and only child status had significant direct effects on their intention to study overseas. The results also identified parents’ education, Level of Institutional Support, Quality of Campus Relationship as significant indirect effects.